Synthesis of Podophyllotoxin and its Derivatives via NiCl2/NaBH4 Reduction of Isoxazoline Ring - Suresh Babu, Meduri; Madhavu Lokanatha Rai, Kuria (Asian Journal of Chemistry, 2013)
A novel synthesis of podophyllotoxin was carried out in four steps. The key step was reduction of isoxazoline ring followed by diazotization and the resultant alkene was treated with Mn(OAc)3/CH3COOK to form podophyllotoxin.